Sharia Financial Inclusion as a Moderating Variable of The Influence of Sharia Financial Literacy on The Decision To Use Sharia Services - Vidya Ramadhan Putra Pratama; Rabiyatul Jasiyah; Yeni Indraningtyas; Liza Utama; Nadjah Thalib (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to analyze the role of Islamic financial inclusion in moderating the relationship between Islamic financial literacy and people's decisions to use Islamic financial services. Amidst the growth of the global Islamic economy, Indonesia faces the challenge of a significant gap between the level of Islamic financial literacy and inclusion. This study uses a quantitative approach with a survey method of Islamic financial service users. Data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) to test the moderating effect. The results of the literature synthesis indicate that high Islamic financial literacy does not automatically increase the decision to use Islamic services without adequate accessibility through financial inclusion. Islamic financial inclusion is predicted to strengthen the positive influence of literacy on consumer decision-making. This study provides a theoretical contribution to the development of consumer behavior theory in Islamic economics and provides practical implications for regulators in formulating a national strategy for Islamic financial inclusion.